SEMANTIC AND LEXIC FORMING OF RELIEF NOUNS IN ENGLISH - Bekzod Farmonov (Journal Park Publishing, 2023)
In this article, among relief nouns in the English language, there are a lot of lexemes, which are both common words and geographical terms. Integral and differential patterns of relief names in the English language are determined and divided into groups representing hill, plain and lowland patterns.
Keywords: River, lake, swamp, mountain, height, earth, mountain, desert.